Coupled Surface and Groundwater Hydrological Modeling in a Changing Climate. Issue 4 (9th November 2017) - Sridhar, Venkataramana; Billah, Mirza M.; Hildreth, John W.
Abstract: Many current watershed modeling efforts now incorporate surface water and groundwater for managing water resources since the exchanges between groundwater and surface water need a special focus considering the changing climate. The influence of groundwater dynamics on water and energy balance components is investigated in the Snake River Basin (SRB) by coupling the Variable Infiltration Capacity (VIC) and MODFLOW models (VIC‐MF) for the period of 1986 through 2042. A 4.4% increase in base flows and a 10.3% decrease in peak flows are estimated by VIC‐MF compared to the VIC model in SRB. The VIC‐MF model shows significant improvement in the streamflow simulation (Nash‐Sutcliffe efficiency [NSE] of 0.84) at King Hill, where the VIC model could not capture the effect of spring discharge in the streamflow simulation (NSE of −0.30); however, the streamflow estimates show an overall decreasing trend. Two climate scenarios representing median and high radiative‐forcings such as representative concentration pathways 4.5 and 8.5 show an average increase in the water table elevations between 2.1 and 2.6 m (6.9 and 8.5 feet) through the year 2042. The spatial patterns of these exchanges show a higher groundwater elevation of 15 m (50 feet) in the downstream area and a lower elevation of up to 3 m (10 feet) in the upstream area. Broadly, this study supports results of previous work demonstrating that integrated assessment of groundwater‐surface water enables stakeholders to balance pumping, recharge and base flow needs and to manage the watersheds that are subjected to human pressures more sustainably. Abstract : Article impact statement: Development and use of multi‐scale models that are coupled to simulate both surface water and groundwater conditions in a changing climate.